Calcitonin and Bone Physiology: In Vitro, In Vivo, and Clinical Investigations - Jingbo Xie; Jian Guo; Zaeema Kanwal; Mingzheng Wu; Xiangyang Lv; Nihal Abdalla Ibrahim; Ping Li; Manal Ali Buabeid; El-Shaimaa A. Arafa; Qingshan Sun (International Journal of Endocrinology)
Calcitonin was discovered as a peptide hormone that was known to reduce the calcium levels in the systemic circulation. This hypocalcemic effect is produced due to multiple reasons such as inhibition of bone resorption or suppression of calcium release from the bone. Thus, calcitonin was said as a primary regulator of the bone resorption process. This is the reason why calcitonin has been used widely in clinics for the treatment of bone disorders such as osteoporosis, hypercalcemia, and Paget’s disease. However, presently calcitonin usage is declined due to the development of efficacious formulations of new drugs. Calcitonin gene-related peptides and several other peptides such as intermedin, amylin, and adrenomedullin (ADM) are categorized in calcitonin family. These peptides are known for the structural similarity with calcitonin. Aside from having a similar structure, these peptides have few overlapping biological activities and signal transduction action through related receptors. However, several other activities are also present that are peptide specific. In vitro and in vivo studies documented the posttreatment effects of calcitonin peptides, i.e., positive effect on bone osteoblasts and their formation and negative effect on osteoclasts and their resorption. The recent research studies carried out on genetically modified mice showed the inhibition of osteoclast activity by amylin, while astonishingly calcitonin plays its role by suppressing osteoblast and bone turnover. This article describes the review of the bone, the activity of the calcitonin family of peptides, and the link between them.